2017
DOI: 10.1002/adv.21921
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bleaching treatment by hydrogen peroxide on chitosan/durian husk cellulose biocomposite films

Abstract: This study covered the preparation and characterization of durian husk cellulose (DHC)-filled chitosan (CS) biocomposite films. The effects of the DHC content and bleaching treatment via hydrogen peroxide (H 2 O 2 ) on the tensile and thermal properties of the CS/DHC biocomposite films were investigated. The results showed that the tensile strength and percentage of elongation at break decreased with increasing DHC contents, but the modulus of elasticity of the CS/DHC biocomposite films increased along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The discarded durian husks usually end up in landfills or burnt which contributed to environmental pollution. From the literature found durian husk actually contains huge amount of lignocellulose fiber and those compositions are similar to wood fiber [11][12]. In regards, this research is underway to utilise durian husk fiber to WPC.…”
Section: Introductionmentioning
confidence: 95%
“…The discarded durian husks usually end up in landfills or burnt which contributed to environmental pollution. From the literature found durian husk actually contains huge amount of lignocellulose fiber and those compositions are similar to wood fiber [11][12]. In regards, this research is underway to utilise durian husk fiber to WPC.…”
Section: Introductionmentioning
confidence: 95%
“…As expected, the tensile modulus of the biocomposites gradually increases with increasing amount of DHF. It is because the modulus of DHF is usually higher than plastic [12]. Therefore, the presence of higher amount of DHF contributed to higher modulus of the PLA/DHF biocomposite.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Thus, by making the PLA in to biocomposite, the addition of natural filler can be partially replace the PLA without influences its biodegradability and highly reduced the cost of final product. Durio zibethinus Murray, also called as durian, the famous fruit among the Southest Asia countries especially in Malaysia, Thailand, Indonesia and Philippine [12]. The durian fruit is made up of 40% of flesh and 60% of husk.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent research works have shown that many natural fibres from agricultural waste have been utilised to produce composite materials, such as durian husk fibre, corn husk fibre and pineapple leaf fibre. [3][4][5][6] From the literature, the corn husk fibre was fabricated into composite materials by mixing with recycled plastic material. 5 However, the study of fabricating composite from corn husk fibre using vacuum assisted resin infusion (VARI) technique has not been reported in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibre absorbs a significant amount of moisture, has poor thermal stability, shows variation in quality, poor interfacial adhesion, and less compatibility with hydrophobic polymer. 4 This is because the natural fibre comprises strong polarised hydroxyl groups in its chemical structure, thus exhibiting hydrophilic characteristic. 10 The poor interfacial bonding between natural fibre and polymer matrix is a main issue that influences the mechanical strength of composite materials.…”
Section: Introductionmentioning
confidence: 99%